Makna Simbolik Upacara Mengayun dalam Masyarakat Mandailing di Desa Sitopayan (Kajian Antropolinguistik) : Penelitian - Nursukma Suri; Rahmi Yulida Harahap; Alya Assyifa Irfani Sani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The mengayun ceremony is one of the cultural heritage traditions of the Mandailing community that is still preserved today as a form of prayer, hope, and expression of gratitude for a child within a family. The implementation of this ceremony consists of several interconnected processes, such as the recitation of verses from the Qur’an, the reading of Barzanji, collective prayers, circling the swing, and the swinging of the child accompanied by hadrah. Among these series of rituals, the slaughtering of an animal dedicated in the child’s name is regarded as equivalent to aqiqah, leading the local community to consider the child as having undergone a stage of purification. This study aims to identify the religious symbolic meanings found in the mengayun ceremony in Sitopayan Village, Portibi Subdistrict, North Padang Lawas Regency, using an anthropolinguistic approach. This research employs an ethnographic method that describes cultural practices, social interactions, and ritual symbols within their natural context. The research method used is qualitative, involving direct observation, interviews with traditional leaders and community members, as well as documentation of the ceremonial sequence. Research data were obtained from informants’ utterances and field observations related to the implementation of the ceremony. The findings indicate that each stage of the mengayun ceremony, from the slaughtering of the animal to the child-swinging procession contains expository, operational, and oppositional meanings. The mengayun ceremony not only functions as a medium for praying for the child’s safety but also strengthens social bonds, reinforces communal solidarity, and preserves Islamic values that are intertwined with the cultural traditions of the Mandailing community.